A comparative analysis of islamic and common laws of contract (2019)
The role of contract in providing basis for man’s affairs in virtually all his endeavours such as spiritual, social, economic and political necessitates its discussion. Comparison between Islamic and Common laws of contract which many works have not been adequately covered becomes expedient for better understanding of our interactions and knowing the more virile that serves the people better. Therefore, this paper analyses and compares the main principles of Islamic and Common laws of contract from the points of view of their coverage and elements. Using inductive qualitative methodology to explore some conceptual frameworks of Islamic sources and textual analysis of the main texts of Islamic and Common laws, the paper found that the rules of Islamic law of contract are very similar to those of common law of contract in the areas of offer, acceptance, mutual consent, terms of contract, pacta sun servada (abiding by stipulation of contract) etc. Tadlīs (fraud), gharar (misinterpretation), etc render contract invalid in both laws. Caveat emptor and caveat venditor are more pronounced in Islamic law than common law. Contracts that involve an insane person during his lucid period, non-Sharī‘ah compliant products and services such as liquor, ribā (interest), gambling are null and void in Islamic law but they are allowed in common law. The paper concludes that the principles of contract are very similar under both laws though some differences exist in their details and applications. People should fulfil their contractual obligations to ensure peaceful coexistence, security, efficient and effective operation of businesses.